Comparative light and scanning electron microscopic studies of pollen of two marijuana species causing allergies. Issue 9 (6th June 2022) - Abbas, Moneeza; Shaheen, Shabnum; Arshad, Amina; Ali, Muhammad; Rasool, Bilal; Rasool, Ghulam
Abstract: Marijuana ( Cannabis ) belongs to family Cannabaceae . This plant is a great natural source of cannabinoids, which have several medical applications such as it is used for the treatment of anxiety and psychosis, disorders of motility and epilepsy. However, this plant is also notorious for its pollen allergic reactions. Mainly two species, that is, C. sativa L. and C.indica Lam. are involved in allergic reactions. In this study, morpho‐palynological studies of both the species were conducted. A number of morphological differences were observed in the both species. C. sativa is tall with narrowed leaves and fibrous stalk plant while C. indica is short, bushier, broad leaves, and having woody stalk plant. Both the species are varied in their pollen characteristics. The polar diameter of C. sativa observed was 7.5 μm and equatorial diameter was 8 μm, and its shape was oblate‐spheroidal. C. indica had 7 μm polar diameter, 7.5 μm equatorial diameter but its shape was similar to C. sativa, that is, oblate‐spheroidal. About 40%‑50% people were affected with both these marijuana species and had symptoms of allergies like dry cough, congestion, itchy eyes, sore throat, nausea, a runny nose, watery eyes, and sneezing. It was concluded that both species' pollen are allergy causing and pollen of both species are different with variations in morphological and allergic symptoms. Research Highlights: Marijuana has great therapeutic importance but it is also notorious for its pollen allergic reactions. Two species of Marijuana, that is, Cannabis sativa L. and Cannabis indica Lam mainly responsible for these pollen allergies. The present research work focused the morpho palynological analysis of these two Marijuana species through light and scanning electron microscopy. Abstract : Palynological analysis of Marijuana species causing allergies.